Recent advances and changing face of anatomy teaching and learning in medical education - Mathew Joseph; Brijendra Singh (Wolters Kluwer Medknow Publications, 2019)
Background A sound knowledge of human anatomy is a maj'or requirement for being a good physician or a practicing surgeon. Despite digitalization and modernization of education sector, traditional cadaveric dissection still occupies the leadership of anatomy education. It is becoming an untold truth that no modern technologies such as virtual dissection or 3D model printing could replace cadaveric dissection in its way of teaching students. Methods Recent research studies on modern anatomical teaching methods for medical and non-medical students and their influences are reviewed. Results Despite new technologies, traditional cadaveric dissection helps students to acquire more practical knowledge and still occupies prior position on its way.